Positioning : the battle for your mind - Ries, Al; Trout, Jack (McGraw Hill-Ascent Audio, 2001)
"Ries and Trout taught me everything I know about branding, marketing, and product management. When I had the idea of creating a very large thematic community on the Web, I first thought of Positioning ..."--David Bohnett, Chairman and Founder of GeoCities A handsome edition of the original 1981 text, this 20th Anniversary Edition makes available to business and marketing professionals-including tens of thousands of Ries and Trout groupies, worldwide-the work that forever changed the way marketing strategy is done. This new edition features commentary from the authors that offers fresh insight into why "positioning" a product in a prospective customer's mind is still the most important strategy in business, and includes numerous examples of campaigns that followed, or didn't follow, Ries and Trout's thinking